Blueberry Phenolics Reduce Gastrointestinal Infection of Patients with Cerebral Venous Thrombosis by Improving Depressant-Induced Autoimmune Disorder via miR-155-Mediated Brain-Derived Neurotrophic Factor - Xu, Ning; Meng, Hao; Liu, Tianyi; Feng, Yingli; Qi, Yuan; Zhang, Donghuan; Wang, Honglei (Frontiers in Pharmacology, 2017)
Cerebral venous thrombosis (CVT) often causes human depression, whereas depression-induced low immunity makes the patients susceptible to gastrointestinal infection. Blueberry possesses antidepressant properties which may improve autoimmunity and reduce gastrointestinal infection. Brain-derived neurotrophic factor (BDNF) performs antidepressant function and can be regulated by miR-155, which may be affected by blueberry. To explore the possible molecular mechanism, blueberry compounds were analyzed by high-performance liquid chromatography. Activity of compounds was tested by using HT22 cells. The present study tested 124 patients with CVT-induced mild-to-moderate depressive symptoms (Center for Epidemiologic Studies—Depression Scale [CES-D] ≥16) and gastrointestinal infection. Patients were randomly assigned to blueberry extract group (BG, received 10 mg blueberry extract daily) and placebo group (PG, received 10 mg placebo daily). After 3 months, depression, gastrointestinal infection and lipid profiles were investigated. Serum miR-155 and BDNF were measured using real-time quantitative polymerase chain reaction and or Western Blot. Blueberry treatment improved depressive symptoms and lipid profiles, and also reduced gastrointestinal infection in the BG group (P < 0.05) but those of the PG group (P = 1). These changes were paralleled by increase in serum levels of BDNF and miR-155 (P < 0.05). HPLC analysis showed that blueberry extracts were the main phenolic acids with 0.18, 0.85, 0.26, 0.72, 0.66, 0.41 and 1.92 mg/g of gentisic acid, chlorogenic acid, [2]-epicatechin, p-coumaric acid, benzoic acid, p-anisic acid, and quercetin in blueberry extracts, respectively. Phenolics in blueberry are possible causal agents in improving antidepressant activity and reducing gastrointestinal infection. Administration of blueberry increased BDNF expression and miR-155. Blueberry cannot affect BDNF level when miR-155 is overexpressed or inhibited. Phenolics from blueberry reduced gastrointestinal infection of patients with cerebral venous thrombosis by improving antidepressant activity via upregulation of miR-155-mediated BDNF.